1988
DOI: 10.1152/ajpcell.1988.254.5.c661
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative potential in developing rat diaphragm, EDL, and soleus muscle fibers

Abstract: To examine the effect of postnatal development on changes in oxidative potential of fibers of specific types (I, IIa, IIb, and IIc) in the rat diaphragm, determinations of succinate dehydrogenase (SDH) activity were made using microphotometric measures of optical density. Samples of the costal region of the diaphragm were extracted from 56 male Wistar rats ranging in age from 8 to 85 days and subgrouped into seven developmental periods (1, 2, 3, 4, 6, 9, and 12 wk). For type I fibers, increases of 17% (P less … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
36
1

Year Published

1989
1989
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 32 publications
9
36
1
Order By: Relevance
“…As in most studies regarding age effects, the present results indicate a fast-to-slow fibre-type transition in soleus muscle, whereas no modification in fibre-type distribution was observed in EDL muscle (Smith et al, 1988;Ishihara and Taguchi, 1991;Sugiura et al, 1992;Konishi et al, 2000;Punkt et al, 2004).…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…As in most studies regarding age effects, the present results indicate a fast-to-slow fibre-type transition in soleus muscle, whereas no modification in fibre-type distribution was observed in EDL muscle (Smith et al, 1988;Ishihara and Taguchi, 1991;Sugiura et al, 1992;Konishi et al, 2000;Punkt et al, 2004).…”
Section: Discussionsupporting
confidence: 72%
“…Fibre-type differentiation is one useful example of this complex period. As a matter of fact, soleus muscle shows gradual fastto-slow fibre differentiation and extensor digitorum longus (EDL) muscle a type IIA-to-IIB differentiation (Smith et al, 1988;Umezu et al, 1992). Then at weaning age, skeletal muscles of rats have a well-defined pattern of fibre type, which are in agreement with their functional profile, e.g.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…In the rat soleus muscle, type A and type C fibers have significantly higher oxidative enzyme activities than type fibers 3,21,44) . In this study, the mRNA expression level of PGC-1 in the soleus muscles of the GK group was lower than that of the WR group (Fig.…”
Section: Discussionmentioning
confidence: 89%
“…Furthermore, F fibers consist of two subtypes with oxidative and glycolytic enzymes: fibers that stain darkly for both oxidative and glycolytic enzymes (FOG), and fibers that stain lightly for oxidative enzymes and darkly for glycolytic enzymes (FG) (PETER et al, 1972). Previous studies (KUGELBERG, 1976;SILLAU and BANCHERO, 1977;RUBINSTEIN and KELLY, 1978;SMITH et al, 1988) have observed that the histochemical differentiation and the type shift of muscle fibers in a muscle occurs during postnatal development. However, there are only a few detailed investigations on the histochemistry of muscle fibers during the early developmental stage.…”
Section: Discussionmentioning
confidence: 99%